Estimating the Effects of Financial Liberalisation on Governability and Social Stability - Chavez, Carlos (Foreign Trade Review, 2024)
This article studies the effects of financial liberalisation on governability. The dependent variables measure governability in terms of control of corruption, government effectiveness, political stability, rule of law, regulatory quality and free speech for 125 countries from 1996 to 2019. As a variable measuring financial liberalisation, I use the Chinn-Ito index and Fernandez index as capital control measure. I use fixed-effects panel data, quantile regression, system GMM and event study to estimate these effects. The results I find show that the financial liberalisation has strong effects on those governability variables, especially low-income countries tend to have a higher sensitivity to changes in capital controls on governability and social stability, as well as countries in the 0.4-0.6 quantiles of the governability. Finally, I find that these effects take at least one year to become persistent over time. These findings imply that, in times of political turbulence and instability, governments may pursue liberalising policies that increase the dynamism of the economy to alleviate the climate of ungovernability.
Keywords: Capital Controls; Governability; Social Stability; Financial Liberalisation